Farmer Risk Preferences and Willingness to Pay for African Rice Landrace Seed: An Experimental Choice Analysis - Arouna, A.; Tyack, N.; Aboudou, R. (CAB International, 2023)
Most literature that investigates the impact of farmer risk preferences on agricultural technology adoption has focused on how risk preferences impact the adoption of technologies that enhance productivity but that may be riskier than local technologies. In this work, we elicit the risk preferences of smallholder rice farmers and investigate how these preferences impact how they value having access to seed of farmers’ varieties of African rice (Oryza glaberrima) maintained in the gene bank of the Rice Biodiversity Center for Africa. These varieties may have lower yields, but they may be more consistent and less risky given their adaptation to the local climatic conditions. We use a Becker–DeGroot–Marschak (BDM) mechanism to elicit farmers’ willingness to pay for small amounts of landrace seed (35 g) in Côte d’Ivoire. We find that farmers generally value having access to African rice landraces (with a mean willingness to pay of ~US$0.50), and that this willingness to pay is influenced positively by loss-aversion preferences (but not risk aversion), along with several other factors. This finding is in contrast with past evidence suggesting that loss aversion is connected to slower adoption of novel technologies, and suggests that the impact of risk preferences on technology adoption may depend on the potential ability of technologies to guard against economic losses.